2020
DOI: 10.3390/microorganisms8040488
|View full text |Cite|
|
Sign up to set email alerts
|

Pectin Degradation is an Important Determinant for Alfalfa Silage Fermentation through the Rescheduling of the Bacterial Community

Abstract: This study aimed to evaluate the effects of the four kinds of additives on the silage quality and the relevant bacterial community diversity by Illumina HiSeq 16S rRNA sequencing. The four kinds of additives were Lactobacillus plantarum (LP), organic acids including gallic acid (GA) and phenyllactic acid (PA), pectin (PEC), and enzymes including pectinase (PEE) and cellulase (CE). After 30 d of fermentation, the pH value was shown to have the lowest value in the PEE and PEC groups, followed by the PA group, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 39 publications
0
15
3
Order By: Relevance
“…The pH and NH 3 -N level of silages are direct indicators of silage quality (Hashemzadeh-Cigari et al, 2014). Compared with the pH and NH 3 -N level was reported in soybean (Ni et al, 2018) and alfalfa silage (Wang et al, 2020), the low pH and NH 3 -N level in all treatment groups in this study confirmed that the corn silage was easily and successfully ensiled due to the high LAB count (5.47 log CFU/g fresh material) and WSC content (10.61% of dry matter). LAB counts of >10 5 CFU/g fresh material FIGURE 3 | Relative abundance of bacterial composition in fresh corn and corn silage at the (A) phylum and (B) genus level.…”
Section: Discussionmentioning
confidence: 93%
“…The pH and NH 3 -N level of silages are direct indicators of silage quality (Hashemzadeh-Cigari et al, 2014). Compared with the pH and NH 3 -N level was reported in soybean (Ni et al, 2018) and alfalfa silage (Wang et al, 2020), the low pH and NH 3 -N level in all treatment groups in this study confirmed that the corn silage was easily and successfully ensiled due to the high LAB count (5.47 log CFU/g fresh material) and WSC content (10.61% of dry matter). LAB counts of >10 5 CFU/g fresh material FIGURE 3 | Relative abundance of bacterial composition in fresh corn and corn silage at the (A) phylum and (B) genus level.…”
Section: Discussionmentioning
confidence: 93%
“…In CTGP, Alternaria (average RA > 10%) was a common plant and animal pathogen [16,44], which correlated negatively with unclassified_f__Enterobacteriaceae, un-classified_k__Fungi, and Naganishia. The addition of probiotics in PTGP decreased the number of nodes (24), coefficient (0.750), heterogeneity (0.407), shortest path length (70), and average neighbor number (2.917) of the correlation network (Figure 6b), which indicated few interactions in PTGP. These results demonstrated that abundant exogenous probiotics directly changed the initial microflora structure so that subsequent microbial diversity and interaction in PTGP was lower than in CTGP.…”
Section: Relationships Between Microflora and Their Physicochemical Characteristicsmentioning
confidence: 99%
“…The inoculation of more nutritious feedstuffs, such as corn, soybean meal, and distiller’s grains with probiotics such as Bacillus subtilis , L. plantarum , and Saccharomyces cerevisiae also enhances their nutritional value in animal feed by increasing CP content, reducing the average protein molecular mass, decreasing the content of antinutritional compounds (such as soybean antigenic proteins glycinin and β-conglycinin), and decreasing lignocellulose content [ 12 , 17 , 21 , 22 ]. Furthermore, the addition of lignocellulose enzymes, such as cellulase and xylanase, alone or in combination with LAB, to the fermentation of food waste for animal feed can enhance the hydrolysis of structural carbohydrates to water-soluble sugars and their subsequent microbial transformation into organic acids [ 23 , 24 ]. The combination of next-generation sequencing (NGS) and bioinformatics systems, such as BugBase and FUNGuild, has been used to investigate the composition and characteristics of complex microbial communities associated with environmental samples [ 23 , 25 , 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…Araújo et al [ 11 ] selected LAB from silage based on their ability to produce a carboxyesterase, an enzyme involved in hydrolysis of fibers, thus improving silage digestibility, or to inhibit the development of the mycotoxin producer Fusarium graminearum. In another study [ 12 ], Lactobacillus supplementation to silage was less efficient than other additives, such as pectin or pectinase, which modulate the rumen microbial diversity towards a higher relative abundance of Leuconostoc , and Bacillus and Aeromonas .…”
mentioning
confidence: 99%